Association of Food Access, Recreational Opportunities, and Natural Amenities with Engagement in the Veterans MOVE! Weight Management Program. Issue 1 (20th December 2019) - Graham, Laura A.; Malone, Emily B.; Richman, Joshua S.; Carson, April P.; Affuso, Olivia; Knight, Sara J.; Levitan, Emily B.
Abstract : Objective: The aim of this study was to examine the association of county‐level food access, recreational opportunities, and natural amenities with participant engagement in a weight management program. Methods: In this cohort study, participants in the Veterans Health Administration MOVE! weight management program between October 1, 2007, and September 30, 2013, were observed for 12 months after enrollment. Engagement was measured as the number of program visits per year at 12 months. Cross‐sectional analysis and spatial regression were used to examine county characteristics associated with greater participant engagement at 12 months. Results: A total of 321, 624 participants in 2, 708 counties were included. Greater engagement was associated with older age, female sex, white race, being married, and being retired. After accounting for similarities between nearby communities, engagement at 12 months was 3.1 visits higher for each additional farmers' market per 1, 000 population ( P  = 0.01). Engagement was highest for participants living in counties with the most natural amenities ( P  < 0.001). Recreational opportunities had only a small effect on engagement in the program (β = 0.02 visits at 12 months; P  = 0.002). Conclusions: Consideration of a participant's county characteristics in addition to other known demographics and program factors may help to explain variation in engagement in weight management programs.